2020
DOI: 10.1002/cmdc.202000642
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Overview of Structure‐Activity Relationships of Small‐Molecule Splicing Modulators Targeting SF3B1 as Anticancer Agents

Abstract: The pre‐mRNA splicing factor SF3B1 shows recurrent mutations among hematologic malignancies and some solid tumors. In 2007, the identification of two cytotoxic natural products, which showed splicing inhibition by binding to SF3b, prompted the development of small‐molecule splicing modulators of SF3B1 as therapeutics for cancer. Recent studies suggested that spliceosome‐mutant cells are preferentially sensitive to pharmacologic splicing modulation; therefore, exploring the clinical utility of splicing modulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 97 publications
(233 reference statements)
0
12
0
Order By: Relevance
“…SF3b1 is directly involved in BPS recognition and hence mutations or small molecules binding in the SF3b1 are known to affect BPS selection, leading to alternative splicing ( Alsafadi et al., 2016 ; Corrionero et al., 2011 ; Darman et al., 2015 ; Maguire et al., 2015 ; Seiler et al., 2018 ; Zhang and Meng, 2020 ). Further, SF3b1 contributes to the regulatory mechanism of alternative splicing by serving as a scaffold for the binding of alternative splicing modulators at its N-terminal extension viz.…”
Section: Resultsmentioning
confidence: 99%
“…SF3b1 is directly involved in BPS recognition and hence mutations or small molecules binding in the SF3b1 are known to affect BPS selection, leading to alternative splicing ( Alsafadi et al., 2016 ; Corrionero et al., 2011 ; Darman et al., 2015 ; Maguire et al., 2015 ; Seiler et al., 2018 ; Zhang and Meng, 2020 ). Further, SF3b1 contributes to the regulatory mechanism of alternative splicing by serving as a scaffold for the binding of alternative splicing modulators at its N-terminal extension viz.…”
Section: Resultsmentioning
confidence: 99%
“…18,19 These studies have led to a remarkable level of structure−activity relationship (SAR) data that defines how each of these molecules adopts a consensus motif that uniquely positions itself into the core SF3B complex of the spliceosome. 20,21 Recognized since their discovery, the high potency and tumor cell selectivity of these analogues has ultimately led to the entry of two Phase I clinical trials on semi-synthetic analogues E7107 (3a, Figure 2) and H3B-8800 (3b). 22,23 While both trials were unsuccessful, the promise of this class remains, and medicinal chemical efforts have continued to tune the metabolic stability and splice modulatory activity of this class, with the ultimate goal of realizing active analogues that can serve either as primary therapeutics or as the active agents in antibody−drug conjugates.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Owing to a growing interest in RNA splicing for drug discovery, a number of studies and patents have been reported, including review articles that (partially) cover the biological features and structure–activity relationship of pladienolides [ 40 , 41 , 42 , 43 , 44 ]. In this review, we provide a comprehensive overview of the total synthesis of pladienolides or their core structures, with a detailed analysis of the synthetic routes.…”
Section: Introductionmentioning
confidence: 99%